In silico study of cytochrome P450 alleles and phenotypic distribution in Vietnamese population - Ngoc Ha, Pham; Phan Tuan, Nguyen; Thi Xuan, Trinh; Nam Hai, Truong; Dang Hung, Tran; Cuong, Nguyen (Vietnam Journal of Biotechnology, 2022)
Cytochrome P450 enzymes play an important role in phase I drug metabolism, accounting for approximately 75% of the enzymatic processes. We investigated the allele and phenotypic distributions of five important CYP genes (CYP2B6, CYP3A5, CYP2C9, CYP2C19, CYP2D6) in the Vietnamese population by using Stargazer and the PharmCAT tool to call star alleles and translating them into phenotypes based on the available dataset of PharmGKB. We compared our computational analysis of the Vietnamese distributions with those of East Asia, Europe, America and other super populations, as well as with previous experimental research. The allele frequencies and phenotypic distributions of the five important CYP genes in the Vietnamese population are similar to those in East Asia while significantly different from other populations. In silico analysis also provided consistent results with previous experimental studies. In addition, the resultant data from our research contributes to the database of genetic variations in pharmacogenetics and constructs the fundamentals for future basic and applied research.